2016
DOI: 10.1097/mcg.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonsteroidal Anti-Inflammatory Drugs in Exacerbations of Inflammatory Bowel Disease

Abstract: GOALS To determine the role of NSAIDs in activation of IBD. BACKGROUND Non-steroidal anti-inflammatory drugs (NSAIDs) may activate inflammatory pathways in inflammatory bowel disease (IBD). STUDY Crohn’s and Colitis Foundation of American (CCFA) Partners is an ongoing cohort study of patients living with IBD. All data are self-reported via the internet. We identified a sub-cohort of participants whose disease activity, based on short Crohn’s Disease Activity Index (sCDAI) and simple clinical colitis activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 18 publications
4
54
0
4
Order By: Relevance
“…A growing body of evidence supports the idea that Hsp27 regulates migration of many cell types, possibly through reorganization and polymerization of the actin cytoskeleton [3537]. COX-2 has been strongly implicated in wound healing, and these findings may partially explain how non-steroidal anti-inflammatory drugs (NSAIDs) may exacerbate IBD [38, 39] or lead to mucosal ulceration [40, 41]. The findings suggest that combination therapies directed at multiple targets may be therapeutically beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the idea that Hsp27 regulates migration of many cell types, possibly through reorganization and polymerization of the actin cytoskeleton [3537]. COX-2 has been strongly implicated in wound healing, and these findings may partially explain how non-steroidal anti-inflammatory drugs (NSAIDs) may exacerbate IBD [38, 39] or lead to mucosal ulceration [40, 41]. The findings suggest that combination therapies directed at multiple targets may be therapeutically beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inherent qualitative differences among studies, we conducted quality assessment using Newcastle‐Ottawa scale (Tables S1 and S2). Studies with a score ≥7 were considered to have low risk of bias, consistent with prior definitions …”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, patients with established IBD are encouraged to avoid the use of NSAIDs because of the concern for their potential adverse effects on disease activity and instead are encouraged to use acetaminophen for management of pain. Although several studies have examined the link between NSAIDs use and IBD exacerbation, the results have been conflicting . We therefore sought to conduct a systematic review and meta‐analysis of prior studies examining the relationship between acetaminophen, NSAIDs and cyclooxygenase (COX‐2) inhibitors use, and risk of IBD exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…141 CD patients who reported regular NSAID use ≥5 times/month were at higher risk of active disease at 6 months. 142 A randomized controlled trial of NSAIDs in quiescent IBD demonstrated that one-third of patients relapsed within 7–10 days of initiating therapy 143 while selective COX-2 inhibitors like celecoxib did not have a similar deleterious effect. 144 …”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%